2011
DOI: 10.1186/1754-6834-4-33
|View full text |Cite
|
Sign up to set email alerts
|

How recombinant swollenin from Kluyveromyces lactisaffects cellulosicsubstrates and accelerates their hydrolysis

Abstract: BackgroundIn order to generate biofuels, insoluble cellulosic substrates are pretreated and subsequently hydrolyzed with cellulases. One way to pretreat cellulose in a safe and environmentally friendly manner is to apply, under mild conditions, non-hydrolyzing proteins such as swollenin - naturally produced in low yields by the fungus Trichoderma reesei. To yield sufficient swollenin for industrial applications, the first aim of this study is to present a new way of producing recombinant swollenin. The main ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 97 publications
6
97
1
Order By: Relevance
“…Consequently, almost all the expansin-like proteins from fungi and bacteria are nowadays tested in vitro on cellulosic materials, for obvious biotechnologically relevant purposes, i.e. to increase the efficiency of bioconversion of lignocellulose to ethanol (Arantes and Saddler 2010;Jäger et al 2011). These objectives are supported by a number of experimental data concerning the synergism with cellulases (Chen et al 2010;Kim et al 2009;Lee et al 2010;Quiroz-Castañeda et al 2011;Wang et al 2010Wang et al , 2011Zhou et al 2011).…”
Section: Introductionmentioning
confidence: 50%
“…Consequently, almost all the expansin-like proteins from fungi and bacteria are nowadays tested in vitro on cellulosic materials, for obvious biotechnologically relevant purposes, i.e. to increase the efficiency of bioconversion of lignocellulose to ethanol (Arantes and Saddler 2010;Jäger et al 2011). These objectives are supported by a number of experimental data concerning the synergism with cellulases (Chen et al 2010;Kim et al 2009;Lee et al 2010;Quiroz-Castañeda et al 2011;Wang et al 2010Wang et al , 2011Zhou et al 2011).…”
Section: Introductionmentioning
confidence: 50%
“…As previous work had suggested that Swollenin can weaken hydrogen bonding within amorphous regions of cellulose and hemicellulose (8,9,12), it is possible that Swollenin promotes fiber fragmentation by weakening hydrogen bonds and enhancing slippage between adjacent chains within fiber dislocations. This weakening of hydrogen bonding and chain slippage might be sufficient to cause fragmentation within certain severe dislocations, but not within the less severe dislocations.…”
Section: Volume 290 • Number 5 • January 30 2015mentioning
confidence: 99%
“…These disruptive proteins include examples from plants (Expansins) (13), bacteria (Expansin-like proteins (14,15) and some carbohydrate binding modules (CBMs) 2 (16)), and fungi * This work was supported by the Natural Sciences and Engineering Council (Swollenin (8,9,12), Loosenin (17), and CBMs (18)). These proteins have also been shown to promote a variety of disruptive effects on cellulosic biomass, including filter paper dispersion, crystallinity reduction, particle size reduction, swelling of cotton fibers, and roughening of cotton fiber surface (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations